2008
DOI: 10.1017/s0963548307008619
|View full text |Cite
|
Sign up to set email alerts
|

A Short Proof of the Hajnal–Szemerédi Theorem on Equitable Colouring

Abstract: A proper vertex colouring of a graph is equitable if the sizes of colour classes differ by at most one. We present a new shorter proof of the celebrated Hajnal-Szemerédi theorem: for every positive integer r, every graph with maximum degree at most r has an equitable colouring with r + 1 colours. The proof yields a polynomial time algorithm for such colourings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 10 publications
(17 reference statements)
0
68
0
Order By: Relevance
“…In a pivotal result, Hajnal and Szemerédi [9] showed that every graph G with maximum degree at most ∆ has an equitable k-coloring for every k ≥ ∆ + 1. Recently, Kierstead and Kostochka [17] have presented a short proof of this result, along with a polynomial-time algorithm for computing such a coloring. Equitable colorings naturally arise in scheduling, partitioning, and load balancing [1,3,12,20,25,26].…”
Section: Weighted Equitablementioning
confidence: 95%
“…In a pivotal result, Hajnal and Szemerédi [9] showed that every graph G with maximum degree at most ∆ has an equitable k-coloring for every k ≥ ∆ + 1. Recently, Kierstead and Kostochka [17] have presented a short proof of this result, along with a polynomial-time algorithm for computing such a coloring. Equitable colorings naturally arise in scheduling, partitioning, and load balancing [1,3,12,20,25,26].…”
Section: Weighted Equitablementioning
confidence: 95%
“…A shorter proof appeared in [38]. Then Kierstead, Kostochka, Mydlarz, and Szemerédi [45] devised an algorithm that in time O(rn 2 ) finds an equitable (r+1)-coloring for any n-vertex graph with maximum degree at most r. It is based on a modification of the proof of Theorem 5.1 in [38].…”
Section: Equitable Coloringmentioning
confidence: 99%
“…Only recently, an alternative algorithmic proof of Theorem 2.4 has been obtained by Mydlarz and Szemerédi [67]. Subsequently, an alternative simple and algorithmic proof has been obtained by Kirstead and Kostochka [47]. Their algorithm employs a clever discharging technique and runs in O(n 5 ) time.…”
Section: H-factors In Graphs With Sufficiently Large Minimum Degreementioning
confidence: 99%